Examination of Paraffin Sections of Different Rainbow Trout (Oncorhynchus mykiss) Tissues by Light and Scanning Electron Microscope - Beste Demirci; Funda Terzi; Osman Sabri Kesbiç (Open Journal of Hepatology - Peertechz Publications, 2022)
The current study aimed to highlight histopathological findings in paraffin block sections of the liver, gill kidney, and pyloric cecum of rainbow trout (Oncorhynchus mykiss) by different imagining devices such as Scanning Electron (SEM) and Light Microscope (LM). To determine the performance of different imagining methods two different thickness paraffin sections such as 5 and 15 µm about various rainbow trout tissue were prepared for imagining different devices. That sections were imagined by SEM and LM, both sections including 5 and 15 µm were imagined by SEM while just 5 µm was an image by LM. In LM imagining, it was detected that hydropic degeneration and vacuole formations in the liver hepatocytes of fish, as well as hyperplasia in bile ducts. Lamellar epithelial cell hyperplasia/hypertrophy was mild and histopathological findings such as secondary lamellar elevation and edema were more severe in rainbow trout gills. Glomerular atrophy/hypertrophy was moderately detected in the kidneys and hydropic degeneration of tubular epithelium was more severe. No degeneration or necrosis was observed in the lamina epithelium of the pyloric cecum. In SEM imagining of different thickness paraffin sections, cartilage and secondary lamellar structure in the gills, glomerulus, and Bowman's capsule structure in the kidneys, and the structure of the pyloric cecum was observed. In the SEM imaging of the paraffin block sections of hepatocytes of the liver, the cell nuclei were determined, and also the grooves in the cytoplasm were thought to be vacuoles. As a consequence, the structural elements of the organ had higher clarity in SEM imaging from paraffin block sections, but the histopathological alterations remained unclear. As a result, SEM imaging of fish tissue is more suited for seeing tissue architecture, although LM imaging is better suited for determining and scoring histopathological variations.